Stronger Together: Do Coral Reefs Enhance Seagrass Meadows “Blue Carbon” Potential? - Guerra-Vargas, Luis Alberto; Gillis, Lucy Gwen; Mancera-Pineda, José Ernesto (Frontiers in Marine Science, 2020)
Seagrass meadows are important for carbon storage, this carbon is known as “blue carbon” and represents a vital ecosystem service. Recently there has been growing interest in connectivity between ecosystems and the potential for connected ecosystems to facilitative ecosystem services. Tropical seagrass meadows are connected to coral reefs, as the reef barrier dissipates waves, which facilitates sediment accumulation and avoid erosion and export. Therefore, coral reefs might enhance the seagrass meadows capacity as a blue carbon sink. We tested this hypothesis through an assessment of blue carbon across a gradient of connected seagrass meadow and coral reef sites. We assessed attributes of seagrass meadows along a transect in addition to classifying the sites as exposed and sheltered. Classification of sites was completed through analyzing wave crest density in photographs and using granulometric evenness index. Organic carbon and organic matter were measured in sediment core samples and within seagrass living biomass (both above and below ground). Lastly, we measured changes in above and below ground traits of seagrass plants across the same sites. Gaps in the reef barrier were linked to high wave disturbance and exposed conditions, whilst barrier continuity to low wave disturbance and sheltered conditions. Organic carbon in sediments was 144 Mg ha-1 in the most sheltered (with reef barrier) and 91 Mg ha-1 in the most exposed (without reef barrier) meadows. Sheltered conditions also showed a redistribution of seagrass biomass to a greater quantity of roots compared to rhizomes. Whilst in exposed conditions the opposite occurred, which could be due to increased rhizome biomass have to enhanced anchorage or greater nutrient availability. This study found that coral reefs facilitate blue carbon potential in seagrass meadows indicating that coral reefs support this important ecosystem service. Also, results suggest that loss of coral reef structure due to bleaching and other stressors will likely result in a reduction of the blue carbon storage capacity of adjacent seagrass meadow. Further research should investigate how combined global and regional stresses may impact on the potential for coral reefs to buffer seagrass meadows, and how these stresses affect the functional traits of seagrass plants.